A Novel Meiosis-Related lncRNA, Rbakdn, Contributes to Spermatogenesis by Stabilizing Ptbp2 - Liu, Wensheng; Zhao, Yinan; Liu, Xiaohua; Zhang, Xiaoya; Ding, Jiancheng; Li, Yang; Tian, Yingpu; Wang, Haibin; Liu, Wen; Lu, Zhongxian (Frontiers in Genetics, 2021)
Spermatocyte meiosis is the cornerstone of mammalian production. Thousands of long noncoding RNAs (lncRNAs) have been reported to be functional in various cellular processes, but the function of lncRNAs in meiosis remains largely unknown. Here, we profiled lncRNAs in spermatocytes at stage I of meiosis and identified a testis-specific lncRNA, Rbakdn, as a vital regulator of meiosis. Rbakdn is dynamically expressed during meiosis I, and Rbakdn knockdown inhibits meiosis in vitro. Furthermore, Rbakdn knockdown in testes in mice by intratesticular injection disturbs meiosis, reduces testicular volume, and increases apoptosis of spermatocytes, resulting in vacuolation of the seminiferous tubules. Rbakdn can bind to Ptbp2, an RNA-binding protein that is important in the regulation of the alternative splicing of many genes in spermatogenesis. Rbakdn knockdown leads to a decrease in Ptbp2 through the ubiquitination degradation pathway, indicating that Rbakdn maintains the stability of Ptbp2. In conclusion, our study identified an lncRNA, Rbakdn, with a crucial role in meiosis.